2019
DOI: 10.1002/uog.20102
|View full text |Cite
|
Sign up to set email alerts
|

Reference ranges for Doppler indices of umbilical and fetal middle cerebral arteries and cerebroplacental ratio: systematic review

Abstract: There is considerable methodological heterogeneity in studies reporting reference ranges for Doppler indices of UA, MCA and CPR, and the resulting references have important implications for clinical practice. There is a need for the standardization of methodologies for Doppler velocimetry and for the development of reference standards, which can be correctly interpreted and applied in clinical practice. We propose a set of recommendations for this purpose. This article is protected by copyright. All rights res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(126 citation statements)
references
References 86 publications
3
120
0
3
Order By: Relevance
“…Three quarters of the published references were performed by one sonographer. Multisonographer observations increase external efficacy and data reliability [53]. The current study was performed by 3 radiologists with long term experience 5-25 years in feto-maternal Doppler ultrasonography (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three quarters of the published references were performed by one sonographer. Multisonographer observations increase external efficacy and data reliability [53]. The current study was performed by 3 radiologists with long term experience 5-25 years in feto-maternal Doppler ultrasonography (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In great numbers of observations, each case was examined at least three times and the study was based on a population that had no pregnancy risk nor complications, and surely, the current study reference ranges are reliable and could be applicable in the general population. Both the median and variance ought to be displayed as a function of gestational age in a way that accounts for the expanding variability with gestation and affords smooth centile curves; goodness of fit testing ought to illustrate that these curves depict precisely the structure of the raw information [53]. The present study created scattered diagram curves of gestational age individual measurements and calculated CPR reference ranges for MCA/UA PSV, S/D ratio, RI, and PI in 1284 observations with 1st-99th percentiles, and 50th percentiles clearly demonstrate our tabulated raw data.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, centiles for the MCA PI and UA PI as well as the CPR have often suffered from methodological flaws such as small sample size, suboptimal modelling and lack of reporting of model diagnostics or subsequent goodness-of-fit evaluation. According to Oros' systematic review on reference centiles for Doppler indices, Ebbings 2007 longitudinal reference ranges were methodologically the most robust that were published to date (93). However, when I applied Ebbings 10 th centile to the Mater obstetric cohort, I found that it was reflective of 20% of our population (i.e.…”
Section: Use Of Routinely Collected Data: Birth Trends Between 2010 -mentioning
confidence: 99%
“…Also, whilst the multilevel modelling adjusts for the correlation within subjects, using the conditional reference intervals based on Royston's 1995 paper, further addresses the issue of bias and the possibility of unusual patterns arising from repeated measurements (89). (72) to be the highest scoring (93). Surprisingly there was no mention or reference to the methodology employed by the WHO for the Intergrowth-21 st project which conducted comprehensive research into appropriate methodology for anthropometry.…”
Section: Centile Creation For Doppler Indicesmentioning
confidence: 99%
See 1 more Smart Citation